Diversity and antibacterial activity of culturable bacteria from rhizosphere soil in seagrass bed halophytes - CHEN Wang'an1,2,3, LI Mi1,2, LI Fangting1,2, GAO Chenghai1,2* (Guangxi Zhiwu)
The purpose of this study was to investigate the novelty and particularly of the culturable bacteria in seagrass bed and study its antibacterial activity crude extracts of the metabolites. A total of nine rhizosphere soil samples were collected from the seagrass bed ecosystems in Pearl Bay and Yuzhouping, Fangchenggang City. Five different isolation media were used to isolate and purify the culturable bacteria using the dilution spread plate method. The bacterial species were identified through PCR amplification and 16S rRNA sequencing. The antibacterial activity against four human pathogenic bacteria(methicillin-resistant Staphylococcus aureus, S. epidermidis, S. aureus and Acinetobacter baumannii)were screened with Kirby-Bauer method. The results were as follows:(1)A total of 42 culturable bacteria were isolated, belonging to 14 genera and 13 families, which included Streptomyces, Vibrio, Bacillus, Shewanella, Microbacterium, Brevibacterium, Staphylococcus, Sphingomonas, Rothia, Psychrobacter, Pseudonocardia, Photobacterium, Halomonas, and Shigella. The genus Streptomyces was the dominant bacterium.(2)Antibacterial activity showed that six bacteria exhibited strong inhibitory activity against at least two or more human pathogenic bacteria, which included Vibrio(1 strain), Rothia (1 strain), and Streptomyces(4 strains). The studies show that the rhizosphere soil microbial resources of halophytes in the seagrass bed in Fangchenggang sea area are novel and unique, and Streptomyces has a strong antibacterial activity, which provides a new source for the research and development of new antibiotics drugs.